2012
DOI: 10.2337/db11-1369
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Coding and Control Region Variants as Genetic Risk Factors for Type 2 Diabetes

Abstract: Both the coding and control regions of mitochondrial DNA (mtDNA) play roles in the generation of diabetes; however, no studies have thoroughly reported on the combined diabetogenic effects of variants in the two regions. We determined the mitochondrial haplogroup and the mtDNA sequence of the control region in 859 subjects with diabetes and 1,151 normoglycemic control subjects. Full-length mtDNA sequences were conducted in 40 subjects harboring specific diabetes-related haplogroups. Multivariate logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 31 publications
6
69
0
Order By: Relevance
“…In our study, the increased mtDNA copy number in the haplogroup B4 was a protective response, which is similar to the protective response of human beings against sepsis either through increased heat generation because of higher electron transport rates or looser coupling [31], or through ROS production to reduce infection [12]. About 96% of our population group, including the B4 cybrid line used in this study, carry T16217C but only 12% carry the additional A16247G, C16261T control region variants [32], [33]. The combinations of these variants are specifically identified as a Polynesian motif, which has also been reported in some of the Chinese population [32].…”
Section: Discussionsupporting
confidence: 76%
“…In our study, the increased mtDNA copy number in the haplogroup B4 was a protective response, which is similar to the protective response of human beings against sepsis either through increased heat generation because of higher electron transport rates or looser coupling [31], or through ROS production to reduce infection [12]. About 96% of our population group, including the B4 cybrid line used in this study, carry T16217C but only 12% carry the additional A16247G, C16261T control region variants [32], [33]. The combinations of these variants are specifically identified as a Polynesian motif, which has also been reported in some of the Chinese population [32].…”
Section: Discussionsupporting
confidence: 76%
“…A study in a Japanese population indicated that M8a and B4c contributed to susceptibility to T2DM or obesity (14), whereas N9a conferred resistance to T2DM in a combined Japanese and Korean population (16), and provided protection against metabolic syndrome in Japanese women (17). By contrast, a recent study in a Taiwanese population with Chinese ethnic backgrounds revealed that subjects harboring the haplogroup B4 had significant morbidity from diabetes, whereas subjects harboring D4 had borderline resistance to T2DM development; however, subjects with N9a did not present significant morbidity or resistance (15).…”
Section: Discussionmentioning
confidence: 80%
“…Mitochondrial haplogroups defined by common polymorphisms are known to be associated with the risk of a variety of diseases, including Leber's hereditary optic neuropathy (27), Alzheimer's disease (28), cardiovascular disease (29) and T2DM (14)(15)(16)(17). It was hypothesized that mitochondrial haplogroups confer the genetic predisposition to develop T2DM when an individual is exposed continuously to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The OriB variant was reported to be associated with type 2 diabetes in Europeans and Asians11192021. However, the effects of the OriB variant may only emerge in a specific environment and/or under a specific nuclear background222324.…”
Section: Discussionmentioning
confidence: 99%